Peran Kualitas Kepemimpinan Kepala Sekolah terhadap Peningkatan Profesionalisme Guru - Nur Indah Mufarrohatul A’yun; M Imamul Muttaqin (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The role of school principals holds crucial significance in enhancing educational quality of education, especially through strengthening and empowering the professionalism of educators. This article discusses the diverse aspects of principal leadership and its effect on teacher performance within the school setting. The principal not only functions as an administrative manager, but also acts as an educator, innovator, as well as a motivator who can guide teachers in realizing educational goals. In their capacity as leaders, school principals have the responsibility to create a positive work culture, provide professional support, and formulate policies and strategies to improve teacher competence. Various efforts to develop teacher professionalism, such as training, certification programs, and advanced studies, are key for improving the quality of teaching in schools. The article also identifies the role of school principals in managing changes and challenges in the world of education, as well as the importance of support from various parties to create an environment that supports teacher development. The results of the study indicate that effective leadership of school principals is able to improve teacher performance, which is further a determinant factor in the success of the education system as a whole.